Methodological Strategies that Influence the Development of the English Language Learning during the Second term, 2020 - Suárez Flores, Elizabeth | Martínez, Wendy Paola | Alvarado, MSc. Mauricio Alvarado MSc. Mauricio (Nicaragua | MATAGALPA UNAN FAREM Matagalpa, 2021)
This research work is about the implementation of visual aids in developing English speaking skills of students of the seventh grade A, afternoon shift at Eliseo Picado Institute, the Matagalpa second term 2020. The aim of the research is to design strategies using visual aids for the development of English speaking skill and identify strategies. Besides it explains how visual aids help to develop English speaking skills of students and propose strategies that utilize visual aids that help teachers develop more communicative and more dynamic classes. Speaking is an essential skill used to communicate and to share thought with other people. Speaking skill is developed through different activities that the teacher conducts in a way that students feel motivated in the classroom. This study is mixed. It is based on quantitative and qualitative approaches. Data were collected using an interview and observation guide to identify the strategies using visual aids in the classroom and a survey to analyze the information obtained by the students. These instruments were analyzed using graphics; findings indicated that most students increased their motivation only through the implementation of strategies such as Dice game, Memory game and Roulette using flashcards. To conclude, the use of common visual aids in the classroom, such as flashcards, drawing and realia are a tool useful to English speaking skills in the students through activities that help increase the motivation and stimulate their participation in the classroom. Keywords: Visual aids, speaking skills, strategies, motivation
Seminario-(Licenciadas en Ciencias de la Educación con mención en Inglés)-Universidad Nacional Autónoma de Nicaragua.
Seminario (Licenciatura en Ciencias de la Educación, con mención en English) Universidad Nacional Autónoma de Nicaragua
Keywords: Estrategias metodológicas&#x0D